Highlighting recent trends in open source geospatial science and software - Mobasheri, Amin; Mitasova, Helena; Neteler, Markus; Singleton, Alexander; Ledoux, Hugo; Brovelli, Maria Antonia (Transactions in GIS, 2020)
Over the past decade, open source software has become widely accepted across governments, industries and academia. The geospatial domain is no exception and this trend is also reflected in geospatial research and practice. Nowadays, governments and stakeholders from the business sector both participate and promote open geospatial science including open geospatial data and open source geospatial software. As a result, open source geospatial science and software (i.e., open source GIS) is a growing area of research with numerous applications and great potential. The consistent prevalence of open source GIS studies motivated this thematic collection. The contributions are divided into two main categories. In the first, novel open source geospatial software and standards are presented, each of which has been implemented for and applied to a certain use case, and at the same time may be applied to other use cases due to the reproducibility of open source software. The second category presents and discusses the applicability and usability of open source GIS solutions for various interdisciplinary domains, mostly related to urban studies.